Bagaimana Tingkat Kepuasan Pengguna KAI Acces? Persepsi Kualitas Pelayanan Online Reservation Ticket - Nanda Zakiyatul A; Zahrotun Nikmah; Rania Rivalda; Alifia Shafara; Khairani Zikrinawati; Zulfa Fahmy (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
Service perception is a form of consumer assessment of a good, service, and or so on. Perceptions of service include service quality and other determinants of use satisfaction, therefore this research was conducted to find out and analyze how perceptions of online reservation ticket service quality influence user satisfaction with KAI Access. The data obtained in this study by distributing questionnaires were then analyzed using quantitative analysis. Sampling in this study were 164 respondents using a non-probability sampling technique, namely purposive sampling. In this study, data processing was assisted by the SPSS version 20 application by testing the assumptions and testing the hypotheses that had been generated. The results of the analysis of the data obtained can be stated that the perception of service quality has a positive influence with an influence size of 25.7% on the satisfaction of KAI Access users in Indonesia, with a significance value of 0.000 <0.05. This means that the better the quality of service owned by KAI Access, the the level of user satisfaction is getting higher. Therefore, companies must always strive to improve and improve service quality so that KAI Access users have a high level of satisfaction.